Get the GIST? An overview of gastrointestinal stromal tumours. (May 2016) - Watson, G.; Kelly, D.; Melland-Smith, M.; Gleeson, J.; McEntee, G.; Kelly, C.; McCaffrey, J.
Abstract GISTs are the most common mesenchymal neoplasms of the gastrointestinal tract. The last 20 years have been revolutionary in the understanding of these tumours and began with the discovery of c-KIT, a proto oncogene that when mutated forms the molecular basis for the growth and development of these malignancies. Surgery was previously considered to be the only treatment modality in both local and advanced disease, however, the introduction of immunotherapy agents such as tyrosine kinase inhibitors has had profound effects on how we now approach and manage these tumours. These novel agents have significantly reduced the frequency of disease recurrence and dramatically improved survival, and serve as a model for the study of targeted therapies in other solid tumors. We present a review of gastrointestinal stromal tumours and consider the current evidence based detection and management of these unique tumors.